2018
DOI: 10.1371/journal.pone.0204248
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationships between perceived individual-level occupational stress and hazardous alcohol consumption among Japanese teachers: A cross-sectional study

Abstract: Most teachers have a high risk of work-related stress and mental disorders. Drunken driving and hazardous alcohol consumption (HAC) among teachers are social problems. Gender differences among teachers in burnout, occupational stress, self-efficacy and job satisfaction were reported. This study aimed to clarify gender differences in the relationships between perceived individual-level occupational stress and HAC among Japanese teachers. A cross-sectional study was conducted in 2013 and a total of 723 male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
1
12
0
5
Order By: Relevance
“…The variance in workload refers to the extent of a marked increase in workload, the amount of concentration required on work tasks, and the speed required to complete work tasks. As for the variance in workload, before the COVID-19 pandemic, previous research indicated that variance in workload was associated with depressive symptoms among Japanese firefighters [ 37 ] and heavy drinking among female Japanese teachers [ 36 ]. However, little research on job future ambiguity and variance in the workload as occupational stress has been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variance in workload refers to the extent of a marked increase in workload, the amount of concentration required on work tasks, and the speed required to complete work tasks. As for the variance in workload, before the COVID-19 pandemic, previous research indicated that variance in workload was associated with depressive symptoms among Japanese firefighters [ 37 ] and heavy drinking among female Japanese teachers [ 36 ]. However, little research on job future ambiguity and variance in the workload as occupational stress has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the NIOSH job stress model [ 30 ], we focused on four subscales (quantitative workload, job control, variance in workload, and job future ambiguity) to evaluate occupational stress. Two subscales were used to evaluate social support (from supervisors and coworkers), which functions as a buffering factor, according to the results of many previous studies on the relationship between psychiatric symptoms and occupational stress [ 20 , 21 , 22 , 23 , 33 , 34 , 35 , 36 , 37 ]. Items on the GJSQ are positively oriented and higher scores indicate lower stress levels for the job control and social support items.…”
Section: Methodsmentioning
confidence: 99%
“…Soltan's study reports that, Gender had no significant association to the mean score of work stress (P > 0.05) (Soltan et al, 2020). These results suggest that, occupational stress is a transgender phenomenon and can affect anyone, male or female (Faraji et al, 2019) whereas Deguchi and Quian disagrees and thinks Gender differences need to be considered when developing stress prevention strategies (Deguchi et al, 2018;Qian et al, 2019). A general possibility exists in older literature in which females experience higher levels of occupational stress regarding gender-specific stressors and have different ways of interpreting and dealing with problems related to their work environment.…”
Section: Gender and Stressmentioning
confidence: 95%
“…As a maladaptive strategy to cope with stress, alcohol use in turn compromises emotional regulation and aggravates emotional distress, perpetuating alcohol use ( Lee et al, 2018 , Wellman et al, 2014 ). Importantly, although men are more likely to engage in binge drinking than women ( Merlo et al, 2017 ) (see ( Wilsnack et al, 2018 ) for increasing rates of female binge drinkers), women appear to be more vulnerable to emotional stress and mood disturbance ( Kuntsche et al, 2017 ) and the effects of stress on alcohol consumption ( Deguchi et al, 2018 ). Thus, it is critical to examine sex differences in the relationship between perceived stress and alcohol use and the neural bases of these differences.…”
Section: Introductionmentioning
confidence: 99%